Closed-Loop Chemical Recycling of a Biobased Poly(oxanorbornene-fused γ-butyrolactone) - Harsevoort, Eva; Cioc, Răzvan C; Lutz, Martin; Thevenon, Arnaud; Bruijnincx, Pieter C A (Journal of the American Chemical Society, 2024)
New polymers, properly designed for end-of-life and efficiently formed from renewable carbon, are key to the transition to a more sustainable circular plastics economy. Ring-opening polymerization (ROP) of bicyclic lactones is a promising method for the production of intrinsically recyclable polyesters, but most lactone monomers lack an efficient synthesis route from biobased starting materials, even though this is essential to sustainably account for material loss during the life cycle. Herein, we present the exceptionally rapid and controlled polymerization of a fully biobased tricyclic oxanorbornene-fused γ-butyrolactone monomer ( ). Polyester P( ) was formed in low dispersity (D̵ = 1.2-1.3) and controllable molecular weight up to = 76.8 kg mol and exhibits a high glass transition temperature ( = 120 °C). The orthogonal olefin and lactone functionalities offer access to a wide range of promising materials, as showcased by postpolymerization modification by hydrogenation of the olefin, which increased polymer thermal stability by over 100 °C. Next to rapid hydrolytic degradation and solvolysis, the poly(oxanorbornene-fused γ-butyrolactone) could be cleanly chemically recycled back to the monomer (CRM), in line with its favorable ceiling temperature ( ) of 73 °C. The density functional theory (DFT)-computed Δ ° of ring-opening with methanol of γ-butyrolactone-based monomers provided a model to predict , and the DFT-computed and X-ray crystal structure-derived structural parameters of , hydrogenated analogue , and regioisomer offered insights into the structural descriptors that cause the high polymerizability of , which is key to establishing structure-property relations.